Fenomena Flexing di Media Sosial dan Kaitannya dengan Israf - Zilal Afwa Ajidin; Nafkhatul Wahidah (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2023)
The phenomenon of flexing has recently become a hot topic of discussion after many influencers and YouTubers show off their wealth with various motives. This study analyzes how Islam views the flexing phenomenon and relates to israf (exaggeration). This study uses a qualitative method with an exploratory approach to literary studies and related sources such as social media. In accordance with the phenomenon of public figures who like to show off their wealth on social media and other public spaces, this study tries to analyze flexing behavior in terms of Islam and its relation to israf behavior. The results of this study show that the act of flexing is an act that is prohibited in Islam because showing off wealth is considered bad in Islamic teachings and includes israf (excessive) behavior.Keywords: flexing, social media, israf